Joint international consensus statement for ending stigma of obesity - Rubino, Francesco; Puhl, Rebecca M.; Cummings, David E.; Eckel, Robert H.; Ryan, Donna H.; Mechanick, Jeffrey I.; Nadglowski, Joe; Ramos Salas, Ximena; Schauer, Phillip R.; Twenefour, Douglas; Apovian, Caroline M.; Aronne, Louis J.; et al. (Nature medicine, 2020)
People with obesity commonly face a pervasive, resilient form of social stigma. They are often subject to discrimination in the workplace as well as in educational and healthcare settings. Research indicates that weight stigma can cause physical and psychological harm, and that affected individuals are less likely to receive adequate care. For these reasons, weight stigma damages health, undermines human and social rights, and is unacceptable in modern societies. To inform healthcare professionals, policymakers, and the public about this issue, a multidisciplinary group of international experts, including representatives of scientific organizations, reviewed available evidence on the causes and harms of weight stigma and, using a modified Delphi process, developed a joint consensus statement with recommendations to eliminate weight bias. Academic institutions, professional organizations, media, public-health authorities, and governments should encourage education about weight stigma to facilitate a new public narrative about obesity, coherent with modern scientific knowledge.